Antibacterial Effect of Silver Nanoparticles Synthesized Using Murraya koenigii (L.) against Multidrug-Resistant Pathogens - Faizan Abul Qais; Anam Shafiq; Haris M. Khan; Fohad M. Husain; Rais A. Khan; Bader Alenazi; Ali Alsalme; Iqbal Ahmad (Bioinorganic Chemistry and Applications)
Development of multidrug resistance among pathogens has become a global problem for chemotherapy of bacterial infections. Extended-spectrum β-lactamase- (ESβL-) producing enteric bacteria and methicillin-resistant Staphylococcus aureus (MRSA) are the two major groups of problematic MDR bacteria that have evolved rapidly in the recent past. In this study, the aqueous extract of Murraya koenigii leaves was used for synthesis of silver nanoparticles. The synthesized MK-AgNPs were characterized using UV-vis spectroscopy, FTIR, XRD, SEM, and TEM, and their antibacterial potential was evaluated on multiple ESβL-producing enteric bacteria and MRSA. The nanoparticles were predominantly found to be spheroidal with particle size distribution in the range of 5–20 nm. There was 60.86% silver content in MK-AgNPs. Evaluation of antibacterial activity by the disc-diffusion assay revealed that MK-AgNPs effectively inhibited the growth of test pathogens with varying sized zones of inhibition. The MICs of MK-AgNPs against both MRSA and methicillin-sensitive S. aureus (MSSA) strains were 32 μg/ml, while for ESβL-producing E. coli, it ranged from 32 to 64 μg/ml. The control strain of E. coli (ECS) was relatively more sensitive with an MIC of 16 μg/ml. The MBCs were in accordance with the respective MICs. Analysis of growth kinetics revealed that the growth of all tested S. aureus strains was inhibited (∼90%) in presence of 32 μg/ml of MK-AgNPs. The sensitive strain of E. coli (ECS) showed least resistance to MK-AgNPs with >81% inhibition at 16 μg/ml. The present investigation revealed an encouraging result on in vitro efficacy of green synthesized MK-AgNPs and needed further in vivo assessment for its therapeutic efficacy against MDR bacteria.